A novel estimate of biological aging by multiple fitness tests is associated with risk scores for age-related diseases - Manca, A.; Fiorito, G.; Morrone, M.; Boi, A.; Mercante, B.; Martinez, G.; Ventura, L.; Delitala, A. P.; Cano, A.; Catte, M. G.; Solinas, G.; Melis, F.; et al. (Frontiers in Physiology, 2023)
Recent research highlights the need for a correct instrument for monitoring the individual health status, especially in the elderly. Different definitions of biological aging have been proposed, with a consistent positive association of physical activity and physical fitness with decelerated aging trajectories. The six-minute walking test is considered the current gold standard for estimating the individual fitness status in the elderly. In this study, we investigated the possibility of overcoming the main limitations of assessing fitness status based on a single measure. As a result, we developed a novel measure of fitness status based on multiple fitness tests. In 176 Sardinian individuals aged 51-80 years we collected the results of eight fitness tests to measure participants' functional mobility, gait, aerobic condition, endurance, upper and lower limb strength, and static and dynamic balance. In addition, the participants’ state of health was estimated through validated risk scores for cardiovascular diseases, diabetes, mortality, and a comorbidity index. Six measures contributing to fitness age were extracted, with TUG showing the largest contribution (beta=2.23 SDs), followed by handgrip strength (beta=-1.98 SDs) and 6MWT distance (beta=-1.11 SDs). Based on fitness age estimates, we developed a biological aging measure using an elastic net model regression as a linear combination of the results of the fitness tests described above. Our newly developed biomarker was significantly associated with risk scores for cardiovascular events (ACC-AHA: r=0.61; p=0.0006; MESA: r=0.21; p=0.002) and mortality (Levine mortality score: r=0.90; p=0.0002) and outperformed the previous definition of fitness status based on the six-minute walking test in predicting an individual health status. Our results indicate that a composite measure of biological age based on multiple fitness tests may be helpful for screening and monitoring strategies in clinical practice. However, additional studies are needed to test standardisation and to calibrate and validate the present results.